Intimate stories told by the grain proteins of Australian wheat and Thai rice .... to the police, to breeders, to grain growers, to grain handlers, to processors and to us as consumers - Wrigley, Colin; Siriamornpun, Sirithon (Food Agricultural Sciences and Technology, 2023)
All cereal grains have genetic (“intimate”) information “locked up” in the grain proteins. Accessing this information requires suitable methods of protein extraction and fractionation. Here we describe how this research approach can reveal information about stolen wheat - reliable evidence to be accepted in court. Plant breeders also rely on the grain-protein “semantides” to predict the type of grain quality (even from just a single grain), thus to produce new varieties of suitable quality. That same semantic information can subsequently be used after harvest to ensure that grain deliveries of the appropriate quality type are binned together, but separate from grain of different quality. Information about the grain proteins is also critical to the processing and consumption of grain-based foods.